Obtaining Environmentally Friendly Encapsulated Mineral Fertilizers Using Encapsulated Modified Pet - Grechanik, Ruslan; Lutek, Wojciech; Malovanyy, Myroslav; Nagursky, Oleg; Tymchuk, Ivan; Petrushka, Kateryna; Luchyt, Liubov; Storoshchuk, Uliana (Видавництво Львівської політехніки, 2022)
The article deals with the study of the prospects for the use of mineral fertilizers encapsulated in PET for bioremediation. This increases efficiency, prevents environmental pollution from undigested plants with plant nutrients, and minimizes the number of application operations. In addition, it disposes of a significant portion of PET waste, the uncontrolled accumulation of which poses a threat to the environment. The basic technological schemes of preparation of a film-forming composition and encapsulation of fertilizers are offered. The kinetic parameters of the process of release of batteries of granulated ammonium nitrate encapsulated with a film based on modified PET are determined.
Keywords: encapsulated mineral fertilizers; PET; nutrients; environmental hazards; release of nutrients